THE UTILIZATION OF ANDROID-BASED ANIMATION VIDEOS ON LEARNING ISLAMIC RELIGIOUS EDUCATION IN SELAYAR ISLAND - Sukriyani S; Muhammad Yaumi; Muhammad Yahdi (JICSA : Journal of Islamic Civilization in Southeast Asian, 2021)
This study examines and examines the use of Android-based animated videos in learning Islamic Religious Education in Elementary Schools, Benteng Islands Selayar District. The purpose of the study was to get an overview of the integration of android-based animation videos and to find a picture of the interaction that was built on the use of android-based animated videos in learning Islamic Religious Education at the Benteng Selayar Elementary School. This type of research is classified as qualitative descriptive with a phenomenological approach. The data sources of this research are the Principal, Islamic Religious Education Teachers, students and parents. The results of the study indicate that the integration of android-based animated videos in Islamic Religious Education learning is that Islamic Religious Education teachers carry out learning using learning media in the form of simple android-based animated videos.